POTENSI KAYU MANIS SEBAGAI TERAPI ALAMI DALAM MENGELOLA DIABETES MELITUS - Abdullah, Dessy; Siti Mubarokah (Nusantara Hasana Journal, 2025)
Type 2 diabetes mellitus (T2DM) is a condition that is increasing globally. Pharmacological therapy often causes side effects, so many studies have begun to explore natural ingredients such as cinnamon as potential companion therapies in diabetes management. This study aims to review the potential of cinnamon as a natural therapy in managing blood sugar levels in patients with type 2 diabetes mellitus. In this study, a literature review method was used by collecting various literature regarding the effect of aromatherapy as an anxiety therapy on students. Study collection was carried out by searching on Google Scholar. The article search technique uses several keywords based on the PICO-S (Population Intervention Compare Outcome-Study Design) technique and specific signs and codes. The keywords obtained are: (1) Cinnamon, (2) Diabetes mellitus, (3) Natural therapy, (4) Diabetes treatment. Article screening was carried out according to inclusion and exclusion criteria. Various studies show that cinnamon can help lower blood sugar levels, increase insulin sensitivity, and improve lipid metabolism. Cinnamon supplementation has the potential to be used as complementary therapy in the treatment of type 2 diabetes mellitus. However, further research is needed regarding the optimal dose and duration for long-term therapy.